2020
DOI: 10.1002/jbm.a.36936
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of cerium dioxide nanoparticles

Abstract: Cerium dioxide nanoparticles (CeO2NPs) with a high value of ζ‐potential (≥30 mV) have been synthesized in reverse microemulsions and they are able to form the high‐stable aqueous suspension without any additional stabilizers. It has been shown that the interaction of such CeO2 NPs with transport proteins, such as BSA, affects their molecular conformation and biochemical activity. The observed changes in the UV‐absorbance spectrum and intrinsic fluorescence quenching of BSA molecule are indicative of the occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
1
17
1
1
Order By: Relevance
“…Native HSA is an α-helical protein . HSA contains 18 Tyrs, 31 phenylalanines (Phes), a lone Trp residue (Trp214), and 17 pairs of disulfide bonds. , The electronic spectrum of individual albumin is characterized by an absorption band at ∼280 nm (Figure a), which is mainly due to protein chromophores, Trp and Tyr, as well as the S–S bonds. , The electronic spectrum of the citrate-stabilized colloidal solution of CeO 2 contains an absorption band, the edge of which is located at ∼400 nm (Figure a) . With an increase in the concentration of CeO 2 NPs, a second maximum appeared in the region 300–320 nm in the spectra of the HSA-CeO 2 NP conjugates (Figure b), and hyperchromism (the increase in optical density values) for the absorption peak of HSA can be observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Native HSA is an α-helical protein . HSA contains 18 Tyrs, 31 phenylalanines (Phes), a lone Trp residue (Trp214), and 17 pairs of disulfide bonds. , The electronic spectrum of individual albumin is characterized by an absorption band at ∼280 nm (Figure a), which is mainly due to protein chromophores, Trp and Tyr, as well as the S–S bonds. , The electronic spectrum of the citrate-stabilized colloidal solution of CeO 2 contains an absorption band, the edge of which is located at ∼400 nm (Figure a) . With an increase in the concentration of CeO 2 NPs, a second maximum appeared in the region 300–320 nm in the spectra of the HSA-CeO 2 NP conjugates (Figure b), and hyperchromism (the increase in optical density values) for the absorption peak of HSA can be observed.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with previously published data: similar conformational changes in the protein molecule caused by interaction with CeO 2 NPs were observed using bovine serum albumin (BSA) as an example. 4 The mechanism of the observed effects was interpreted as follows: the loading of a BSA molecule with CeO 2 NPs leads to the separation of protein globules and the partial opening of the albumin domain structure, while two Trp residues and part of the Tyr residues located in the internal hydrophobic cavities of native albumin become accessible to solvent molecules and electromagnetic radiation. 4 At the same time, there were no bathochromic or hypsochromic shifts, which enables the assumption of the absence of protein dissociation.…”
Section: Physicochemical Characteristics Of Ceo 2 Nps and Hsa-ceo 2 Npmentioning
confidence: 99%
See 1 more Smart Citation
“…Que was docked into the binding site of FOXO3A (Figure 8a,b). FOXO3A, a transcription factor, has been reported to reduce oxidative stress in ischemia–reperfusion models by enhancing the activity of superoxide dismutase 25 . The phenyl group of Que was located at the hydrophobic pocket formed by the Ala169, Pro174, Leu178, and Trp186 residues and formed multiple hydrophobic interactions (Figure 8b).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a variety of ROS‐responsive materials have been synthesized and studied, including thiols, thioketals, hydroquinones, metallocenes, polypyridine ruthenium complexes, and thioethers 24 . Increasing studies reported that ROS‐based nanomaterials can be used to treat myocardial ischemia–reperfusion injury 25,26 . In our previous study, we reported ROS‐responsive lipids (Di‐S‐PC) composed of thioether phosphatidylcholines in which the fatty acid chain of a typical lipid is replaced by two tails with thioether linkages 27 .…”
Section: Introductionmentioning
confidence: 99%